CRESCIMENTO DE MUDAS DE JAMBO EM DIFERENTES SOMBREAMENTOS E SUBSTRATOS - COSTA, Geany Giovana Silva; COSTA, Edilson; SILVA, Eliamara Marques; CHAGAS, Paulo Henrique Menezes; BARBOSA, Willams Ferreira Souza; JORGE, Marçal Henrique Amici (ANAIS DO ENIC, 2017)
-